2010
DOI: 10.1007/s12177-011-9066-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lacrimal plugs combined with deproteinized calf blood extract eye gel for filamentary keratitis

Abstract: This study aims to investigate the efficacy of lacrimal plugs combined with deproteinized calf blood extract eye gel on the treatment of dry-eye-associated filamentary keratitis. Lacrimal plugs were inserted into both the upper and lower puncta of 15 patients (28 eyes). Deproteinized calf blood cxtract eye gel was applied in two patients who were not cured after this operation. All patients were asked to complete three questionnaires 1 day before the surgery and at 1 week and 1 month after the surgery. Ophthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The therapy for CPE was standardized and included sodium hyaluronate eye drops and de-proteinized calf blood extract eye gel 4 times a day [ 25 ]. All patients were examined within 3-7 days of the initiation of treatment and at a similar interval thereafter untill healing was complete.…”
Section: Methodsmentioning
confidence: 99%
“…The therapy for CPE was standardized and included sodium hyaluronate eye drops and de-proteinized calf blood extract eye gel 4 times a day [ 25 ]. All patients were examined within 3-7 days of the initiation of treatment and at a similar interval thereafter untill healing was complete.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Deproteinized calfblood extract can significantly alleviate the irritating sensation caused by corneal ulcer; it remains to be unknown whether this extract has an effect on the promotion of corneal neovascularization. [10] Studies have confirmed that [11,12] the application of deproteinized calfblood extract to eyes can improve local hypoxia and ischemic conditions and promote the repair and regeneration of nerve tissues, which is beneficial to the repair of corneal epithelium injury caused by surgery and inflammation. The eye gel, formulated with carboxymethyl cellulose sodium, can pro-long the contact time of drug with the ocular surface, deploy medicinal properties of deproteinized calfblood extract to the greatest effect, simultaneously lubricate the cornea and effectively improve the comfort degree of medication.…”
Section: Resultsmentioning
confidence: 99%
“…20,[22][23][24][25] Punctal occlusion, blepharoplasty, botulinum toxin for temporary tarsorrhaphy, and soft bandage contact lens may also be used depending on the cause of the FK. [26][27][28]…”
Section: Filamentary Keratitismentioning
confidence: 99%